Intrinsic and extrinsic motivation as extralinguistics factors in second language learning among foreign students in five universities of Malaysia - Kamaruddin, Rohaidah; Sha’ri, Sharil Nizam; Ahamd Ghazali, Aqmar Hayati; Hamdan, Rahimah (David Publishing Company, 2017)
Research on the relationship of second language extralinguistic factors with Malay language achievement among foreign students at university in Malaysia is still deficient. Being aware of this fact, the researchers have conducted a study on dominant second language extralinguistic factors in learning a second language. Researchers are keen to study the motivation as one of the main factors in extralinguistic. As a continuation of these efforts, researchers are trying to analyze the most dominant factor in the intrinsic and extrinsic motivation in learning a second language. The sample consists of a group of foreign students from University Putra Malaysia, University Kebangsaan Malaysia, University Malaya, University Teknologi Malaysia, and University Sains Malaysia. The total of 150 samples was from 27 countries. The results of observations and field studies show that foreign students choose Question 5 as the dominant intrinsic motivation variable. When foreign students have a problem understanding something in their Malay language class, they always ask their teachers for help. This indicates that the level of their dependence on teachers is high. Meantime, for extrinsic motivation, the students choose Question 11 as the dominant variable in motivation. For foreign students, studying Malay language is important because they will be able to interact more easily with native speaker of Malay language. Overall, intrinsic motivation among foreign students is at the highest level compared to extrinsic motivation.